An integral terminal sliding mode control scheme for speed control system using a double-variable hydraulic transformer. (May 2022) - Shen, Wei; Wang, Jiehao
Abstract: In recent years, with the aggravation of energy crisis and environmental pollution, the Common Pressure Rail (CPR) system with great energy saving potential has become a research hotspot in the hydraulic research area. However, as the key component of CPR system, hydraulic transformers have the problems of low efficiency and poor control effect, which limit its practical application. The main contribution of the paper is to propose a new type of double-variable hydraulic transformer (DVHT) and address the control issue. As the displacement is adjustable, DVHT can achieve pressure regulation while maintaining the cylinder speed in the high-efficiency area. According to the system characteristics, a new control strategy is designed for the two control variables, and an adaptive integral terminal sliding mode controller is proposed to guarantee the robustness of the system. The simulation results prove the feasibility of the DVHT and show that the control method can achieve multitasking control and effectively improve the control effect.